ANALISIS PENDAPATAN USAHATANI PADI SAWAH DAN PENENTUAN HARGA JUAL BERAS PADA TINGKAT PETANI DI KABUPATEN MOROWALI - Putu Yenata; Made Antara; Max Nur Alam (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
This research purpose was to identify the income of wetland rice farming and the proper rice selling price at the farmer level in Morowalidistrict that can generate good income for the farmers.  Samples of this research were 93 respondents randomly taken from the total population of 1,354 wetland rice farmers with an assumption that all farmers have similar land area sizes.  The results of analysis showed that the income of one farmer is IDR. 12,15,.004/ha/planting season while the TPP analysis revealed that the income is IDR 808,366.53/ha/planting season and the production is 144, 48 kg/ha/planting season.  The selling price determined based onregional minimum wage in Central Sulawesi is IDR 6,713/kg. The Sajogyocriterion is IDR 10,289/kg while the World Bank indicator is IDR 7,657/kg. The rice selling price based on the World Bank indicator is lower than the highest retail price but is higher than the government purchase price. Keywords: Income Analysis, the Determination of Selling Rice, Paddy Field.